Noradrenergic modulation of space exploration in visual neglect. - Malhotra, P; Parton, A; Greenwood, R; Husain, M (2006)
Visual neglect after stroke is often associated with a failure to explore contralesional space. Here, we show that guanfacine, a noradrenergic agonist that modulates dorsolateral prefrontal cortex, improves leftward space exploration in selected right-hemisphere patients with neglect. The positive effects of guanfacine were associated with extended ability to maintain attention on task. The results suggest that neuropharmacological targeting of intact frontal areas might be one way to enhance cognitive function after damage to posterior brain regions in selected individuals.